Ecosystem Legitimacy Emergence: A Collective Action View - Thomas, Llewellyn D. W.; Ritala, Paavo (Journal of management, 2022)
Ecosystems—communities of interdependent yet hierarchically independent heterogeneous participants who collectively generate an ecosystem value proposition—often emerge through collective action, where ecosystem participants interact with each other and the external environment. When such organizational forms are emerging, they require legitimacy to overcome the “liability of newness.” Adopting a collective action lens and taking a legitimacy-as-process approach, we propose a process model of ecosystem collective action, where an orchestrator, complementors, users, and external actors together drive ecosystem legitimacy. We identify three key legitimation processes—discursive legitimation, performative legitimation, and ecosystem identity construction—and demonstrate how these three processes together facilitate the emergence of ecosystem legitimacy and reduce the liability of newness of emerging ecosystems.